2022
DOI: 10.1155/2022/2238320
|View full text |Cite
|
Sign up to set email alerts
|

Influence of SERPINA1 Gene Polymorphisms on Anemia and Chronic Obstructive Pulmonary Disease

Abstract: Background. Anemia is one of the predominant hematological conditions, whereas chronic obstructive pulmonary disease (COPD) is a predominant respiratory disease. These two diseases were found to be interlinked, but the physiological pathways are still unclear. Aim. The current study has been aimed at analysing the genetic interrelationship between anemia and COPD in accordance with different altitudes. Methodology. The genetic analysis was performed in the SERPINA1 gene of anemia, COPD, and healthy individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In active smokers, living at high altitudes is associated with an accelerated decline in lung function [ 16 ]. Inhabitants living at high altitude on a long-term basis have undergone genetic changes, which affect regulation of breathing [ 8 ]. Genome-wide scans of Tibetans have identified candidate genes involved in adapting to high-altitude hypoxia [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In active smokers, living at high altitudes is associated with an accelerated decline in lung function [ 16 ]. Inhabitants living at high altitude on a long-term basis have undergone genetic changes, which affect regulation of breathing [ 8 ]. Genome-wide scans of Tibetans have identified candidate genes involved in adapting to high-altitude hypoxia [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…People at high altitudes have to endure lower partial pressures of O 2 , cold ambient temperatures, lower ambient humidity, and limited access to medical resources. Compared to individuals living in low-altitude areas, high-altitude residents have undergone physiological and/or genetic changes in their respiratory and circulatory systems [ 7 , 8 ]. Owing to the specific characteristics of these populations, using an FR may not be appropriate for people at high altitudes.…”
Section: Introductionmentioning
confidence: 99%
“…The research results of J TBjerrum et al showed that, PDZK1IP1 has the ability to distinguish UC from Crohn's colitis [17], but the pathway by which PDZK1IP1 induces UC needs further experiments to determine. SERPINA1 is the main member of the serine protease inhibitor family and is related to the occurrence of various diseases such as anemia and chronic obstructive pulmonary disease [18]. Peishan Qiu et al have found that SERPINA1 is a central gene related to active UC autophagy and is related to active UC autophagy.…”
Section: Discussmentioning
confidence: 99%